Nitrogen speciation and transformations in fire-derived organic matter - Torres Rojas, Dorisel; Hestrin, Rachel; Solomon, Dawit; Gillespie, Adam W.; Dynes, James J; Regier, Tom Z; Lehmann, Johannes (Elsevier, 2020)
Vegetation fires are known to have broad geochemical effects on carbon (C) cycles in the Earth system, yet limited information is available for nitrogen (N). In this study, we evaluated how charring organic matter (OM) to pyrogenic OM (PyOM) altered the N molecular structure and affected subsequent C and N mineralization. Nitrogen near-edge X-ray absorption fine structure (NEXAFS) of uncharred OM, PyOM, PyOM toluene extract, and PyOM after toluene extraction were used to predict PyOM-C and -N mineralization potentials. PyOM was produced from three different plants (e.g. Maize-Zea mays L.; Ryegrass-Lollium perenne L.; and Willow-Salix viminalix L.) each with varying initial N contents at three pyrolysis temperatures (350, 500 and 700 °C). Mineralization of C and N was measured from incubations of uncharred OM and PyOM in a sand matrix for 256 days at 30 °C. As pyrolysis temperature increased from 350 to 700 °C, aromatic CN in 6-membered rings (putative) increased threefold. Aromatic CN in 6-membered oxygenated ring increased sevenfold, and quaternary aromatic N doubled. Initial uncharred OM-N content was positively correlated with the proportion of heterocyclic aromatic N in PyOM (R2 = 0.44; P < 0.0001; n = 42). A 55% increase of aromatic N heterocycles at high OM-N content, when compared to low OM-N content, suggests that higher concentrations of N favor the incorporation of N atoms into aromatic structures by overcoming the energy barrier associated with the electronic and atomic configuration of the C structure. A ten-fold increase of aromatic CN in 6-membered rings (putative) in PyOM (as proportion of all PyOM-N) decreased C mineralization by 87%, whereas total N contents and C:N ratios of PyOM had no effects on C mineralization of PyOM-C for both pyrolysis temperatures (for PyOM-350 °C, R2 = 0.15; P < 0.27; for PyOM-700 °C, R2 = 0.22; P < 0.21). Oxidized aromatic N in PyOM toluene extracts correlated with higher C mineralization, whereas aromatic N in 6-membered heterocycles correlated with reduced C mineralization (R2 = 0.56; P = 0.001; n = 100). Similarly, aromatic N in 6-membered heterocycles in PyOM remaining after toluene extraction reduced PyOM-C mineralization (R2 = 0.49; P = 0.0006; n = 100). PyOM-C mineralization increased when N atoms were located at the edge of the C network in the form of oxidized N functionalities or when more N was found in PyOM toluene extracts and was more accessible to microbial oxidation. These results confirm the hypothesis that C persistence of fire-derived OM is significantly affected by its molecular N structure and the presented quantitative structure-activity relationship can be utilized for predictive modeling purposes.